Melting behaviour of uranium-americium mixed oxides under different atmospheres. (January 2020) - Epifano, E.; Prieur, D.; Martin, P.M.; Guéneau, C.; Dardenne, K.; Rothe, J.; Vitova, T.; Dieste, O.; Wiss, T.; Konings, R.J.M.; Manara, D.
Highlights: The very high melting temperatures of (U, Am)-oxides (T > 2500 K) were measured. The effect of the oxidation on the melting behaviour was studied. Extensive post-melting characterizations were performed (SEM, XAS). A CALPHAD thermodynamic modeling of the liquid in the U-Am-O system was obtained. Abstract: In the context of a comprehensive campaign for the characterisation of transmutation fuels for next generation nuclear reactors, the melting behaviour of mixed uranium-americium dioxides has been experimentally studied for the first time by laser heating, for Am concentrations up to 70 mol. % under different types of atmospheres. Extensive post-melting material characterisations were then performed by X-ray absorption spectroscopy and electron microscopy. The melting temperatures observed for the various compositions follow a markedly different trend depending on the experimental atmosphere. Uranium-rich samples melt at temperatures significantly lower (around 2700 K) when they are laser-heated in a strongly oxidizing atmosphere compressed air at (0.300 ± 0.005) MPa, compared to the melting points (beyond 3000 K) registered for the same compositions in an inert environment (pressurised Ar). This behaviour has been interpreted on the basis of the strong oxidation of such samples in air, leading to lower-melting temperatures. Thus, the melting temperature trend observed in air is characterized, in the purely pseudo-binary dioxide plane, by an apparent maximum melting temperature around 2850 K for 0.3 < x(AmO2 ) < 0.5. The melting points measured under inert atmosphere uniformly decrease with increasing americium content, displaying an approximately ideal solution behaviour if a melting point around 2386 K is assumed for pure AmO2 . In reality, it will be shown that the (U, Am)-oxide system can only be rigorously described in the ternary U-Am-O phase diagram, rather than the UO2 -AmO2 pseudo-binary, due to the aforementioned over-oxidation effect in air. Indeed, general departures from the oxygen stoichiometry (Oxygen/Metal ratios ≠ 2.0) have been highlighted by the X-ray Absorption Spectroscopy (XAS). Finally, to help interpret the experimental results, thermodynamic computations based on the CALPHAD method will be presented.